2009
DOI: 10.1111/j.1600-0404.1993.tb04244.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical pathology and treatment strategies in Alzheimer's disease: Emphasis on the cholinergic system

Abstract: The neurochemical pathology of Alzheimer's disease (AD) has been consistently shown to involve cholinergic degeneration in the cerebral cortex. This together with evidence from experimental animal studies showing that cholinergic neurones play a role in learning and memory processes has formed the basis of the cholinergic hypothesis of Alzheimer's dementia and the major rationale for neurotransmitter replacement therapy of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…It has been recently reported that extracts from some plants exhibit inhibitory activity against acetylcholinesterase (AChE) . AChE is the principal enzyme involved in the hydrolysis of acetylcholine; therefore, these AChE inhibitors are being developed for the symptomatic treatment of Alzheimer’s disease , . Alzheimer’s disease is a progressive degenerative neurological disorder, which is principally characterized by impaired memory and disturbed behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently reported that extracts from some plants exhibit inhibitory activity against acetylcholinesterase (AChE) . AChE is the principal enzyme involved in the hydrolysis of acetylcholine; therefore, these AChE inhibitors are being developed for the symptomatic treatment of Alzheimer’s disease , . Alzheimer’s disease is a progressive degenerative neurological disorder, which is principally characterized by impaired memory and disturbed behavior.…”
Section: Introductionmentioning
confidence: 99%
“…AChE enzyme is responsible for degrading the neurotransmitter acetylcholine in the synaptic cleft and is often related to the onset of AD (13). One approach for the treatment of this disease would be to retain the normal levels of acetylcholine in the brain with the help of AChE inhibitors (24).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronen (Frim et al, 1994;Shults et al, 1995). Im Gegenteil dazu zeigte eine Studie, in der die BDNF Expression inhibiert wurde, dass dopaminerge Neurone vermehrt zerstört wurden (Porritt et al, 2005) (Davies and Maloney, 1976;Winblad et al, 1993). An dieser Stelle wird eine Funktion des BDNF in der Pathogenese dieser Erkrankung vorgeschlagen, da dieses Neurotrophin in der Lage ist auf cholinerge Neurone zu wirken.…”
Section: Brain Derived Neurotrophic Factor (Bdnf)unclassified